Integrasi Idea Management System (IMS) Berbasis Web untuk Mendukung Implementasi Perbaikan Berkelanjutan (Kaizen) - Budi, Agung Kuncoro; Safuan, Safuan (Jurnal Pendidikan Indonesia, 2025)
In the era of digital transformation, organizations must continually seek improvement to maintain competitiveness and operational efficiency. The Kaizen approach, which emphasizes gradual improvement and active employee participation, requires support from an information system capable of managing ideas systematically and measurably. This study aims to examine how the integration of a web-based Idea Management System (IMS) can support the implementation of Kaizen within organizations. A case study method with a descriptive qualitative approach was employed, utilizing data from observations, system documentation, and interviews with IMS users in a corporate environment. The findings indicate that IMS serves as a strategic medium for channeling improvement ideas from operational levels (Gemba) to management, while also enhancing employee participation in the innovation process. The system facilitates faster idea validation, easier progress tracking, and fosters a culture of continuous improvement. With features such as transparency, notifications, and a reward mechanism, IMS reinforces internal motivation for employees to contribute to efficiency and quality enhancement. This study recommends integrating the development of IMS into organizational knowledge management and digital transformation strategies to maximize the impact of Kaizen implementation.